“I Don’t Understand English Reading”: Utilizing Webtoon as Edutainment Medium to Foster Students’ Reading Comprehension - Esti Ristia Widiyarti; Agus Rofi’i; Rama Dwika Herdiawan; Noermanzah Noermanzah (LP4MK STKIP PGRI Lubuklinggau, 2021)
The demands of 21th century forced students to master in English reading. Yet, the problems faced by the students in reading comprehension still become the reason of alleviation in university level. Therefore, webtoon expected to be the medium that can foster students’ reading comprehension. This experimental study aims to investigate the effect of using webtoons in teaching reading comprehension in English. The design of this research was quasi-experimental. The research sample consisted of the 33 students of X TKL/A (class A of Electricity Department) as sample of experimental class and 36 students of X TKL/C (class C of Electricity Department) as sample in control class. Multiple choice type of test was given to the student and collected as the data of this research. Based on the result of data analysis, the alternative hypothesis is accepted which is there is significant effect used webtoon in teaching reading at the first grade of vocational state school in Majalengka. The data analysis showed that mean score in experimental class that utilized webtoon as medium was higher than control class that used printed narrative text only as medium. The independent t-test result also showed that tcount was higher than ttable (2.019>2). In brief, webtoon as edutainment medium is effective to foster students’ reading comprehension especially in reading narrative text.